Cumulative Effects of Spontaneous Mutations for Fitness in Caenorhabditis: Role of Genotype, Environment and Stress - Baer, Charles F. (Copyright © 2006 by the Genetics Society of America, 2006)
It is often assumed that the mutation rate is an evolutionarily optimized property of a taxon. The relevant mutation rate is for mutations that affect fitness, U, but the strength of selection on the mutation rate depends on the average effect of a mutation. Determination of U is complicated by the possibility that mutational effects depend on the particular environmental context in which the organism exists. It has been suggested that the effects of deleterious mutations are typically magnified in stressful environments, but most studies confound genotype with environment, so it is unclear to what extent environmental specificity of mutations is specific to a particular starting genotype. We report a study designed to separate effects of species, genotype, and environment on the degradation of fitness resulting from new mutations. Mutations accumulated for >200 generations at 20° in two strains of two species of nematodes that differ in thermal sensitivity. Caenorhabditis briggsae and C. elegans have similar demography at 20°, but C. elegans suffers markedly reduced fitness at 25°. We find little evidence that mutational properties differ depending on environmental conditions and mutational correlations between environments are close to those expected if effects were identical in both environments.